2005
DOI: 10.1093/rpd/nci274
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of skyshine computational methods

Abstract: A variety of methods employing radiation transport and point-kernel codes have been used to model two skyshine problems. The first problem is a 1 MeV point source of photons on the surface of the earth inside a 2 m tall and 1 m radius silo having black walls. The skyshine radiation downfield from the point source was estimated with and without a 30-cm-thick concrete lid on the silo. The second benchmark problem is to estimate the skyshine radiation downfield from 12 cylindrical canisters emplaced in a low-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…To separate the cosmic components, both primary and secondary, from the terrestrial and skyshine contributions, measurements were made on the Columbia River at a sufficient distance from land so that air scatter (skyshine) from ground sources and direct terrestrial radiation were negligible. It is reported that skyshine falls off to <0.01% at about 600 m from a source [8]. The boat was anchored in ~10 m of water at a position that was >1000 m laterally from land and any structures (location shown in Figure 6).…”
Section: Cosmic Component Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…To separate the cosmic components, both primary and secondary, from the terrestrial and skyshine contributions, measurements were made on the Columbia River at a sufficient distance from land so that air scatter (skyshine) from ground sources and direct terrestrial radiation were negligible. It is reported that skyshine falls off to <0.01% at about 600 m from a source [8]. The boat was anchored in ~10 m of water at a position that was >1000 m laterally from land and any structures (location shown in Figure 6).…”
Section: Cosmic Component Measurementmentioning
confidence: 99%
“…Skyshine from terrestrial sources has been considered a negligible contributor in most detection applications. However, skyshine from man-made sources on the ground, including accelerators [6], medical sources [7] and industrial sources [8] has disrupted specialized detection efforts in the surrounding area. This has been a recent concern in areas such as the ongoing effort to detect illicit nuclear sources at US border crossings and seaports.…”
Section: Introductionmentioning
confidence: 99%
“…These industrial sources of skyshine radiation can, however, dramatically affect sensitive radiation-detection instrumentation. Published results on skyshine show that the intensity of skyshine drops off exponentially with distance [3]. Additionally, the skyshine spectrum is dramatically shifted to lower energies from photon scattering, with spectra following an exponential drop in that intensity with energy.…”
Section: Radiography Sourcesmentioning
confidence: 99%
“…This is not true for sensitive radiation detection instrumentation. Published results on skyshine show that the intensity of skyshine drops ofT slowly: 10% at --100 m, 1% at --200 m, 0.1% at 400 m, and 0.01% at --600 m [2].…”
Section: Radiography Sourcesmentioning
confidence: 99%